Heterozigosidade em ciclos de seleção do composto CMS 43 de milho pipoca (Zea mays L.) utilizando marcadores microssatélites - Santos, Juliana Franzoni dos (2008)
The BRS Angela variety was developed from the compound CMS-43 after seven intrapopulational recurrent selection cycles, from four recombination cycles from 33 materials of white grains from the Active Germoplasm Bank (BAG). This compound was produced by the Brazilian Empress of Agropecuary Research (EMBRAPA) Maize and Sorghum (National Center of Maize and Sorghum Research - CNPMS) of Sete Lagoas, Minas Gerais. To the present study eight selection cycies was assessed to the compound CMS-43 and named C0, C1, CII, CIII, CIv, Cv , CvI and CvIB. To the genetic evaluation the genomic DNA was extracted from the leaves of the plants in each of the selection cycles. For the assessment of variability and genetic distance the microsatellite marker was used; for the choice of the polymorphic markers between the evaluated lines, 100 microsatellites that have been mapped to common maize were tested. From those markers 20 pairs of primers were selected. With these primers 52 alleles were produced with an average number of alieles per polymorphic locus equal to 2.6. At Cmj cycle it was noticed the loss of 5 alieles (46 alleles), featuring a reduction of 9.80% to the alleles in relation to the C0 cycie (51 alieles). The observed heterozygosity between cycle selections ranged from 20.67% at CvIB cycle to 34.29% at C cycle. Of the 20 loci, two (Umc2261 e Umc1318) had negatives values to Fis index, and the values for the two loci were -0.0868, -0.2745 respectively indicating an excess of heterozygotes even in the face of the recurrent selection process. For the 20 microsateilite loci evaluated in this study, nine of them presented Hardy-Weinberg equilibrium at the last selection cycle (C). This result indicates that, despite the great selection pressure exerted to the desirable characteristics, these loci still is behaving as if the crosses were occurring randomly. This result indicates that it is stiil possible to occur to selection gains made iii new recurrent selection cycles to the BRS Angela variety.